Heavy metal concentrations in the soils and shrubs near a metal processing plant in Peninsular Malaysia. - Chua, S.Y.; Hashim, Nor Rasidah (IUP Publications., 2008)
Industrial areas pose pollution risks because the emissions of heavy metals from these sources are normally high. This study was conducted to determine the concentrations of selected heavy metals (zinc, chromium and copper) in the soils and leaves of a shrub species, Melastoma malabathricum around a metal processing plant. Soil samples were taken in three directions away from the source. After soil digestion using the aqua regia method, the total concentration of each heavy metal was determined using Atomic Absorption Spectrometer (AAS). Leaf samples were taken from one plant per location whenever available. Prior to heavy metal determination using AAS, the foliar samples were prepared using the dry ash method.